2012
DOI: 10.1007/s10803-012-1598-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Infertility Associated with Childhood Autism?

Abstract: Concerns persist about a possible link between infertility and risk of autism spectrum disorders (ASD). Interpretation of existing studies is limited by racial/ethnic homogeneity of study populations and other factors. Using a case-control design, we evaluated infertility history and treatment documented in medical records of members of Kaiser Permanente Northern California. Among singletons (349 cases, 1,847 controls), we found no evidence to support an increase in risk of ASD associated with infertility. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
2
29
0
1
Order By: Relevance
“…Infertility 37 and advanced parental age 24,28 can be associated with long IPI and are Values are expressed as n (%). HR adjusted for maternal age, paternal age, and child gender.…”
Section: Discussionmentioning
confidence: 99%
“…Infertility 37 and advanced parental age 24,28 can be associated with long IPI and are Values are expressed as n (%). HR adjusted for maternal age, paternal age, and child gender.…”
Section: Discussionmentioning
confidence: 99%
“…132 Since then, two studies have found a positive association between assisted reproductive technology use and ASD, 133,134 whereas five studies have found none. 131,[135][136][137][138] However, significant positive associations were found among subgroups such as women over age 34, 136 multiple births 137 and those exposed to specific assisted conception methods.…”
Section: Assisted Conceptionmentioning
confidence: 98%
“…Depuis, deux études ont fait état d'un lien positif entre le recours à la procréation médicalement assistée et le TSA 133,134 , tandis que cinq autres n'en ont trouvé aucun 131,[135][136][137][138] . On a toutefois constaté l'existence de liens positifs importants entre certains sous-groupes, comme les femmes de plus de 34 ans 136 , les naissances multiples 137 et les sujets exposés . Depuis, les conclusions se contredisent 102,124,139,141,144,145 , même si certaines de ces études n'ont pas établi de distinction entre le diabète gravidique et le diabète antérieur à la grossesse.…”
Section: Caractéristiques Des Parentsunclassified